1994
DOI: 10.1002/jcp.1041600122
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of angiogenesis by tissue inhibitor of metalloproteinase

Abstract: Matrix proteases play a critical role in cell invasion and migration, including the process of angiogenesis. The ability of specific factors to induce angiogenic responses correlates with their stimulation of matrix protease synthesis and release. Using an in vivo angiogenesis assay, the endothelial cell response to known angiogenic factors, basic fibroblast growth factor (bFGF) and adipocyte conditioned medium, was blocked by an inhibitor of matrix metalloproteinase activity, TIMP-1. The TIMP effect was media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
1
6

Year Published

1996
1996
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(114 citation statements)
references
References 66 publications
4
103
1
6
Order By: Relevance
“…MMP inhibitors, both synthetic and endogenous, inhibit angiogenic responses both in vivo and in vitro. [37][38][39][40] Moreover, MMPdeficient mice show delayed or diminished angiogenic responses during development or in response to tumor xenograft. 41 But on the other hand, it was reported that MMP-based proteolysis of the ECM proteins releases cryptic fragments, which are very potent anti-antiogenic substances such as angiostatin 42 and endostatin.…”
Section: Inhibition Of Obesity By Angiogenesis Inhibitormentioning
confidence: 99%
“…MMP inhibitors, both synthetic and endogenous, inhibit angiogenic responses both in vivo and in vitro. [37][38][39][40] Moreover, MMPdeficient mice show delayed or diminished angiogenic responses during development or in response to tumor xenograft. 41 But on the other hand, it was reported that MMP-based proteolysis of the ECM proteins releases cryptic fragments, which are very potent anti-antiogenic substances such as angiostatin 42 and endostatin.…”
Section: Inhibition Of Obesity By Angiogenesis Inhibitormentioning
confidence: 99%
“…These zinccontaining enzymes are actively involved in the degradation of the extracellular matrix, and hence act as key-players in tumor invasion and spread. Moreover, there is evidence that these enzymes play a role in the angiogenesis process [46]. Kumar et al advanced the hypothesis that radiotherapy leads to overexpression of type-IV collagenases in rectal cancer (especially MMP-2 and MMP-9) [44].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested that the ability of specific factors to induce angiogenic responses correlates with their stimulation of matrix protease synthesis in endothelial cells (Gross et al, 1982;Montesano and Orci, 1985). For example, antibodies to interstitial collagenase inhibit endothelial cell invasion (Montesano and Orci, 1985), and metalloprotease inhibitors, such as TIMP, inhibit the angiogenic process (Johnson et al, 1994). We have previously shown that microvessel density and ST3 expression do not correlate in breast cancer (Linder et al, 1997), suggesting that the mechanisms that induce ST3 expression are distinct from those that induce angiogenesis.…”
Section: Results Bfgf Staining Patterns In Breast Carcinomamentioning
confidence: 99%